2020
DOI: 10.3390/agronomy10020293
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Proper Application Rate of Nitrogen under Mulched Drip Irrigation to Improve the Yield and Quality of Tomato in Saline Soil

Abstract: Xinjiang is one of the most prolific tomato-planting areas in China. Here, we carried out a two-year (2017–2018) field experiment in Xinjiang to study the effects of different nitrogen (N) application rates on the spatial distribution of water and salt in the root zone, as well as their impacts on the yield and quality of tomatoes under mulched drip irrigation. The ideal ranges of N application rates for tomato yield and quality were examined under different salinity levels. Results indicated that soil water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Biomass accumulation, reflecting the plant life-sustaining activities, is an optimum indicator for evaluating various stresses on plants [47]. Vermicompost increased the plant dry matter accumulation and yield of the tomato plant under salt stress (Figures 3A and 9A), which is consistent with the results observed in rice [55] and wheat [17]. Root activity decreased under salt stress but significantly increased by VM application (Figure 3C).…”
Section: Discussionsupporting
confidence: 87%
“…Biomass accumulation, reflecting the plant life-sustaining activities, is an optimum indicator for evaluating various stresses on plants [47]. Vermicompost increased the plant dry matter accumulation and yield of the tomato plant under salt stress (Figures 3A and 9A), which is consistent with the results observed in rice [55] and wheat [17]. Root activity decreased under salt stress but significantly increased by VM application (Figure 3C).…”
Section: Discussionsupporting
confidence: 87%
“…The three sampling zones in the cotton field were located at 1 4 , 1 2 , and 3 4 of the diagonal distance from the northeast corner to the southwest corner of the field (Figure 1d). All sampling zones were marked after the first sampling to ensure consistency.…”
Section: Sampling Processes and Methodsmentioning
confidence: 99%
“…Sustainable and efficient utilization of saline-alkaline soils is a critical step toward increasing the amount of arable land and its agricultural production capacity, protecting food security in many parts of the world, including maintaining a minimum of 1.8 billion acres of crop production in China [1]. The saline-alkaline soil area in Xinjiang is 1.23 × 10 6 ha, which accounts for nearly one third of total saline-alkaline soil in China [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, soil salinity may disturb the balance of nitrogen, calcium, potassium, phosphorus, iron, zinc, and boron in plants, cause imbalances in nutrition or interfere with nutrient uptake [ 7 , 9 , 10 ]. Soil salt plays a major role in affecting the fluorescence parameters, yield, and quality of most processing tomatoes compared to nitrogen, and reducing nitrogen could obtain higher yields in areas with high salinity [ 11 , 12 ]. It has been reported that saline water ice performs better than freshwater ice due to it increasing the yield of rice and saving freshwater resources [ 13 ].…”
Section: Introductionmentioning
confidence: 99%